Characterization of non-treated sawdust and ionic liquid-treated sawdust - Nor Salihah Abdul Manas (2017)
Biomass pre-treatment can be done with ionic liquid (IL) and this study is certainly use one type of ionic liquid namely 1-butyl-3-methylimidazolium chloride ([BMIM]CL). In this study the sawdust was treated with ([BMIM]CL) as a process of chemical treatment. In this study, sawdust was treated with ([BMIM]CL) at different temperature and different treatment time as the changing parameters. The temperatures were 80℃ 100C 120℃ and the range of treatment time is 24 hours and 48 hours. The Tga analysis was done with the FT-IR and the Xrd analysis. The results showed that the higher temperature used, the higher chances for the decompose of the sawdust occur and the treatment time also not suitable to be longer than 24 hours.